2018
DOI: 10.1038/s41598-018-34237-6
|View full text |Cite
|
Sign up to set email alerts
|

Triciribine increases LDLR expression and LDL uptake through stabilization of LDLR mRNA

Abstract: Low-density lipoprotein receptor (LDLR) is a key regulator of the metabolism of plasma low-density lipoprotein cholesterol (LDL-C), the elevated levels of which are associated with an increased risk of cardiovascular disease. Therefore, enhancing LDLR expression represents a potent treatment strategy for hypercholesterolemia. Here, we report that in cultured human hepatoma cells, triciribine, a highly selective AKT inhibitor, increases the stability of LDLR mRNA, an event that translates into upregulation of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 51 publications
2
27
0
1
Order By: Relevance
“…To examine the effect of these inhibitors on LDLR gene transcription, we cultured HepG2 cells that were transfected with the pLR1563-luc plasmid, a luciferase reporter construct driven by the LDLR promoter, in the absence or presence of the AKT inhibitors for 14 h and then examined them for luciferase activity. As expected, luciferase activity was induced in cells that were treated with MK-2206, whereas triciribine had no effect on luciferase activity (Fig 2B) [16, 17]. Interestingly, all the other AKT inhibitors also exerted a positive effect on luciferase activity.…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…To examine the effect of these inhibitors on LDLR gene transcription, we cultured HepG2 cells that were transfected with the pLR1563-luc plasmid, a luciferase reporter construct driven by the LDLR promoter, in the absence or presence of the AKT inhibitors for 14 h and then examined them for luciferase activity. As expected, luciferase activity was induced in cells that were treated with MK-2206, whereas triciribine had no effect on luciferase activity (Fig 2B) [16, 17]. Interestingly, all the other AKT inhibitors also exerted a positive effect on luciferase activity.…”
Section: Resultssupporting
confidence: 67%
“…We have recently shown that two pharmacologic inhibitors of AKT, MK-2206 and triciribine, increase the levels of LDLR mRNA, leading to increased levels of cell-surface LDLRs [16, 17]. Interestingly, we found that MK-2206 and triciribine utilize two different regulatory mechanisms to trigger the accumulation of LDLR mRNA.…”
Section: Introductionmentioning
confidence: 90%
“…Small molecule-induced stabilization of LDLR mRNA represents a very attractive approach to increase LDLR protein expression in order to treat hypercholesterolemia. Previous studies reported that the LDLR mRNA is labile, but that it can be stabilized in the presence of different small molecule compounds, such as berberine [ 5 ], canadine [ 11 ], AICAR [ 14 ], gemfibrozil [ 29 ], chenodeoxycholic acid [ 8 ] and triciribine [ 12 ]. While the mechanism of LDLR mRNA stabilization by canadine and gemfibrozil is still unknown, triciribine (TCN) shares similarities to berberine, AICAR, and chenodeoxycholic acid by stabilizing LDLR mRNA through an ERK1/2-dependent pathway, and involve the LDLR 3′UTR [ 5 , 8 , 12 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was reported that TCN increases LDLR levels by preventing the degradation of LDLR mRNA in an ERK activity-dependent manner [ 12 ]. This work aimed to elucidate the mechanism that underlies this property of TCN.…”
Section: Introductionmentioning
confidence: 99%
“…12) Simultaneously, ubiquitin-USP16 REGULATES THE STABILITY AND FUNCTION OF LDLR specific protease (USP) 2, one of the deubiquitinating enzyme (DUB), regulates the LDLR pathway by counteracting the E3-ubiquitin ligase IDOL. [13][14][15][16] However, regulation of deubiquitylases in cholesterol metabolism has remained elusive. The widespread pathogenicity of LDL is urgently required for a better understanding of this mechanism, as well as exploring new therapeutic approaches.…”
mentioning
confidence: 99%